Kontribusi Usahatani Sawi Hijau terhadap Pendapatan Petani di Desa Bangli, Kecamatan Baturiti, Kabupaten Tabanan - LESTARI, NI MADE DWI WAHYUNI; ARTINI, NI WAYAN PUTU; YUDHARI, I DEWA AYU SRI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2023)
The Contribution of Grenn Mustard Farming to Farmer’s Income in Bangli Village, Baturiti District, Tabanan Regency.  Mustard greens (Brassica juencea L.) is a type of vegetable that is very popular among consumers.  Green mustard besides being used as a vegetable food ingredient, it can also be used for the treatment of various diseases that have an important role in meeting the food, nutritional, and medicinal needs of the community. This study aims to examine the cost structure of green mustard farmers' income and analyze the contribution of mustard farming to farmers' incomes in Bangli Village, Baturiti District, Tabanan Regency.The sampling technique used is Random Sampling.  The methods used in obtaining data in this study are observation (observations), interviews (interviews) and Library Research. The population in this study were all green mustard farmers in Bangli Village. With the number of green mustard farmers as many as 180 people. Data analysis was carried out by calculating the cost structure of mustard green farming. These results indicate that the average fixed costs incurred in mustard green farming are Rp101,259, while the average variable costs are Rp2,103,162 and the contribution of green mustard farming which is included in the medium category is 43.18% with an area of 0,04 ha. Suggestions that need to be considered are Subak Abian Bangli Village maintain green mustard farming and develop by utilizing technology in green mustard farming in order to be able to improve the quality of high-quality green mustard.